Pretransplant Donor-Specific Anti-HLA Antibodies and the Risk for Rejection-Related Graft Failure of Kidney Allografts - Michiel G. H. Betjes; Kasia S. Sablik; Henny G. Otten; Dave L. Roelen; Frans H. Claas; Annelies de Weerd (Journal of Transplantation)
Background. The presence of donor-specific antibodies (DSAs) against HLA before kidney transplantation has been variably associated with decreased long-term graft survival. Data on the relation of pretransplant DSA with rejection and cause of graft failure in recipients of donor kidneys are scarce. Methods. Patients transplanted between 1995 and 2005 were included and followed until 2016. Donor-specific antibodies before transplantation were determined retrospectively. For cause, renal transplant biopsies were reviewed. Results. Pretransplant DSAs were found in 160 cases on a total of 734 transplantations (21.8%). In 80.5% of graft failures, a diagnostic renal biopsy was performed. The presence of pretransplant DSA (DSApos) increased the risk of graft failure within the first 3 months after transplantation (5.2% vs. 9.4%) because of rejection with intragraft thrombosis (p<0.01). One year after transplantation, DSApos recipients had an increased hazard for antibody-mediated rejection at 10 years (9% DSAneg vs. 15% DSApos, p=0.01) with significant decreased graft survival at 10 years (79% DSAneg vs. 69% DSApos, p=0.02). This could largely contribute to an increased graft loss because of antibody-mediated rejection in the DSApos group. The incidence and graft loss because of T cell-mediated rejection was not affected by the presence of pretransplant DSA. Conclusions. Pretransplant DSAs are a risk factor for early graft loss and increase the incidence for humoral rejection and graft loss but do not affect the risk for T cell-mediated rejection.